DESIGNING INTEGRATED ZAKAT-WAQF MODELS FOR DISASTER MANAGEMENT - Sulistyowati, Sulistyowati (Journal of Islamic Monetary Economics and Finance, 2018)
This study aims to analyze four previous conceptual models related to zakat and waqf by Indrawan et al. (2018), Ascarya et al. (2018), Tanjung (2018), Hassan (2010) and also designing various Integrated Zakat and Waqf Models for disaster management and evaluate them as best model which is most suitable in community, local, and national scopes. In-depth interviews and literature study from relevant sources are conducted to develop the models. The proposed models called Integrated Zakat and Waqf Model for Disaster Management (IZWDM) that involves of social and commercial aspects provides of three alternative models according to three steps of disaster management namely IZWDM-A for Relief step; IZWDM-B for Recovery step; and IZWDM-C for Reconstruction step. This study is expected to enhance all parties to do more synergy in managing disasters that happened in Indonesia.